Saturday

April 19, 2014

April 19, 2014

Posted by **KEll** on Wednesday, April 23, 2008 at 11:58am.

f (x) = 4²x - 5x + 9

a) (2) b) (-3a)

- MAth -
**Reiny**, Wednesday, April 23, 2008 at 12:14pm"Find each of the indicated function value"

implies you want 4²x - 5x + 9 = 2

or do you want to find f(2) ?

I have a feeling it is the second interpretation.

if f(x) = 4²x - 5x + 9

f(2) = 4(2)^2 - 5(2) + 9

= 15

f(-3a) = 4(-3a)^2 - 5(-3a) + 9

= 36a^2 + 15a + 9

Your next posting has the same kind of questions.

**Related Questions**

Math - 2. Find the LCM and GCD of (2y^2 - 3a^2)x + (2a^2 - 3x^2)y and (2a^2 + ...

math - Function k(x) = x+18 Find k(0) k(x) = 6x k(-2) k(5) k(-2) indicated ...

calculus - Consider the following. y = x2 − 9x x2 + 5x at (3, − 3 4...

calculus - I have three questions I'm having a terrible time with: 1)Find, if ...

Math - Use the functions f(x)=1/8x-3 and g(x)=x^3 to find the indicated value or...

math - find the numerical deriviative of the given function at the indicated ...

calculus - Use the intermediate value theorm to show that the polynomial ...

calculus - Find the average value of the function f(x)=8x^2-5x+6 , on the ...

algebra - Given f(x) = 2x - 5, find f(-3a). F(x)= 2(-3a) -5 F(-3a) = 2(3a)-5 = 1...

Last two CALC questions. :) - 8. If f(x) = sin(7 − 5x), find f′(&#...